Experimental testing in 3-point bending of sandwich beams using additively manufactured loading bars - Andrei NENCIU; Dragos Alexandru APOSTOL; Dan Mihai CONSTANTINESCU (INCAS Bulletin)
This study investigates the feasibility of custom-made 3D-printed loading bars of a testing machine and compares their performance to that of standard (metal) components through the 3-point bending testing of sandwich beams. Specifically, the study evaluates two types of sandwich beams: honeycomb and re-entrant unit cell topologies. Each type of beam was subjected to three-point bending tests using both standard and 3D-printed loading bars. The experiments indicate that the printed custom-made loading bars used as a testing accessory are a viable alternative. Further research with a larger number of samples is needed to address the potential of generating a possible defect during the printing process and its propagation during testing.